PHP Objects, Patterns, and Practice - Zandstra, Matt (Apress, 2012)
When I first had the idea for PHP Objects, Patterns, and Practice, I felt I was swimming against the tide. Many pattern implementations in PHP felt like glorified workarounds due to limitations in the language. These days, though, it can be hard to keep up with pace of innovation in PHP objects, design, and project practice. If that's a problem, well, it's the kind you want to have. Especially if you have the tools at hand to navigate the risks and opportunities that present themselves. PHP continues to tick items off the object-oriented developer's wish list. Since the last edition of this book, we have seen namespaces make it into the language, late static binding, anonymous functions, and closures (if those don't yet mean anything to you, don't worry, they're all covered by this book). PHP is an active language, constantly evolving to meet the needs of its users.